Platelet‑rich plasma as a promisinginnovation in dentistry: An epigrammaticoutlook - Suvarna, Suraj; Sahoo, Sukant; Gupta, Anurag; Kumar, Prince (Nigerian Journal of Basic and Clinical Sciences, 2026)
Sir, Guided bone regeneration is a well‑accepted surgical technique utilized in implant dentistry to increase the quantity and quality of the host bone in areas of localized alveolar defects. The lack of predictability in regenerative bony procedures with various grafting materials suggests that enhancement in the osteoinductive properties of these materials are highly desirable. Platelet‑rich plasma (PRP), has become a valuable adjunct in wound healing in clinical dentistry, which is generally prepared from the concentrated suspension of the growth factors found in platelets of the patient and used to deliver these growth factors in high concentration to sites requiring osseous grafting.